Effects of Late Pleistocene Climatic Fluctuations on the Phylogeographic and Demographic History of Japanese Scad (Decapterus maruadsi) - Wang, Qing-Hua; Wu, Ren-Xie; Li, Zhong-Lu; Niu, Su-Fang; Zhai, Yun; Huang, Min; Li, Biao (Frontiers in Marine Science, 2022)
The Late Pleistocene-Holocene climate fluctuations have greatly influenced the phylogeographic structure and historical dynamics of many marine organisms in the western Pacific marginal seas. Here, we investigated the impact of Pleistocene glacial-interglacial cycles on the phylogeographic structure and demographic dynamics of Decapterus maruadsi, an economically important fish along the coast of the East China Sea (ECS) and northern South China Sea (NSCS). We obtained 430 concatenated sequences (Cyt b + control region, 1548–1554 bp) of D. maruadsi, including 246 newly sampled from the ECS and 184 previously determined from the NSCS. Genetic structure and phylogenetic analysis demonstrated a lack of significant population structure among 16 populations. Moreover, there was no significant differentiation among populations from Chinese coastal waters and northern Vietnam. Neutrality tests, unimodal mismatch distributions, Bayesian skyline plots, and the star-like haplotype networks all indicated a recent demographic expansion for D. maruadsi population during the Late Pleistocene-Holocene, explaining the low genetic diversity in D. maruadsi along the southeast coast of China. Notably, phylogenetic analyses and net genetic distances based on Cyt b jointly confirmed that 57 Cyt b haplotypes identified as D. maruadsi from the previously defined Sundaland-Rosario-Ranong clade actually represented D. russelli. These results not only reveal the complex effects of Pleistocene-Holocene climate fluctuations on the phylogeographic structure and demographic history of D. maruadsi but also provide useful genetic information for the management of genetic resources.